The Landscape of the Tumor Microenvironment in Skin Cutaneous Melanoma Reveals a Prognostic and Immunotherapeutically Relevant Gene Signature - Zhou, Sitong; Sun, Yidan; Chen, Tianqi; Wang, Jingru; He, Jia; Lyu, Jin; Shen, Yanna; Chen, Xiaodong; Yang, Ronghua (Frontiers in Cell and Developmental Biology, 2021)
Background: The tumorigenesis of skin cutaneous melanoma(SKCM) is still a mystery. It is well known that the tumor microenvironmen(TME) plays a vital role in the onset and progression of SKCM. Different signals from the microenvironment may promote or inhibit recurrence and metastasis in SKCM. Our study conducted a comprehensive analysis of the immune cell infiltration in the TME. Methods: We analyzed the immune cell infiltration in two independent cohorts, and then assessed the relationship between the internal pattern of immune cell infiltration and SKCM characteristics, including clinicopathological features, potential biological pathways and gene mutations. We further divided the three clusters of differential genes into two groups with different unique biological processes. The Signature gene-A gene set was mainly manifested as exon skipping(ES) in SKCM, while the Signature gene-B gene set has no obvious alternative splicing form. Subsequently, we not only analyzed the genetic variation of the two signatures, but also constructed a ceRNA regulatory network. The correlation between the risk score and the clinicopathological characteristics of SKCM patients indicated that the low risk score was associated with TME Cluster-A classification (P <0.001) and metastatic SKCM (P <0.001). 13 hub genes also showed different prognostic effects in pan-cancers. Univariate and multivariate Cox analysis results showed that risk score can be used as an independent risk factor for predicting the prognosis of SKCM patients The nomogram that integrated clinicopathological characteristics and immune characteristics to predict survival probability is based on multivariate Cox regression. 13 Hub genes showed different prognostic effects in pan-cancers. The IHC staining results showed that Ube2L6, SRPX2, IFIT2 were higher expression while CLEC4E, END3, KIR2DL4 were lower expression in 25 melanoma specimens. Conclusion: We performed a comprehensive assessment of the immune-associated tumor microenvironment (TME). To implicated the potential development of immunogenomics features in SKCM, we constructed an unprecedented set of immune characteristic genes (EDN3, CLEC4E, SRPX2, KIR2DL4, UBE2L6, IFIT2) related to the immune landscape of TME. These genes are related to the different prognosis and drug response of SKCM.The immune gene signature we constructed can be used as robust prognostic biomarkers of SKCM and the predictor of immunotherapy effect.